Bone Age Measurement in Pediatric Patients of Universitas Airlangga Hospital from January 2018 to December 2019 - Dinda Chandra Yuliantari; Anggraini Dwi Sensusiati; Ahmad Suryawan; Muhammad Faizi (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2022)
Highlights:1. There was a significant relationship between bone age calculated by the Tanner Whitehouse II method (TW2-20) and chronological age.2. There was a slowdown in bone age in pediatric patients at Universitas Airlangga Hospital (RSUA). AbstractIntroduction: Bone age is an indicator of biological and skeletal maturity in individuals. It is different from chronological age which is calculated based on the time of birth. The differences in chronological age and bone age can indicate abnormalities in bone development. This study aimed to determine the profile of bone age in pediatric patients at Universitas Airlangga Hospital and the relationship between bone ages examined using the Tanner Whitehouse II (TW2-20) method and their chronological ages.Methods: This was a cross-sectional observational analytic study. Secondary data were collected from medical records and X-Ray examination results from Department of Radiology Universitas Airlangga Hospital (RSUA) Surabaya from January 2018 to December 2019. The data of age, gender, and history of illness were taken. From the collected X-ray results, bone age was examined using the TW2-20 method. Then, a normality test was performed using the Shapiro-Wilk for data less than 50 samples. The results showed that the data were normally distributed (p = 0.419). Data processing of the difference between bone age and chronological age was performed using the parametric paired T-test with a confidence level of 95%.Results: 32 samples were obtained from pediatric patients undergoing X-ray examinations from January 2018 to December 2019. The average bone age difference in male patients was 0.64 years old with the highest average difference found in the age range of 9-11.99 years old. The average bone age difference in female patients was 1.1 years old with the highest average difference found in the age range of 12-14.99 years old. There was a significant difference between bone age calculated using the TW2-20 method and chronological age (p < 0.001).Conclusion: Based on the comparison of the average bone age in pediatric patients and their chronological age, all samples showed deceleration of bone age in pediatric patients at RSUA. Based on the analytical study, the TW2-20 method was not suitable for the sample examined.